An Inticetus-like (Cetacea, Odontoceti) cheek tooth from the Pietra Leccese (Miocene, Southern Italy) - Emanuele Peri; Alberto Collareta; Gianni Insacco; Giovanni Bianucci (Università di Firenze. Dipartimento di Scienze della Terra, 2018)
• We report the find of an Inticetus-like cheek tooth from the Miocene of southern Italy. • We identify this specimen as belonging to cf. Inticetus sp. • This finding brings evidence of faunal exchanges between the Mediterranean Sea and the Pacific Ocean. • This faunal exchange likely happened via the Central America Seaway.